Emergency left colonic resections on an acute surgical unit: does subspecialization improve outcomes?. Issue 10 (21st May 2015) - Gibbons, Genevieve; Tan, Chuan Jin; Bartolo, David C. C.; Filgate, Rhys; Makin, Greg; Barwood, Nigel; Wallace, Marina
Abstract Background Left‐sided colonic pathologies requiring emergency resection are commonly encountered on an acute surgical unit. Subspecialist colorectal (CR) management of these patients may result in decreased morbidity, mortality and stoma rates. This study is the first of its kind comparing outcomes between CR surgeons and general surgeons on an acute surgical unit. Methods This is a retrospective review of 196 consecutive patients who underwent emergency left colonic resection on an acute surgical unit between January 2009 and July 2014. Patients were divided into two groups dependent on whether their surgery was managed by a CR specialist or general surgeon. Primary outcome measures were 30‐day mortality, rate of primary anastomosis and overall stoma rate. Results Patients in the two groups were comparable for age, sex, American Society for Anesthesiologists score as well as CR POSSUM scores. Rates of primary anastomosis were significantly higher in the CR group compared with the acute surgical unit group (85.5 versus 28.7%, P ≤ 0.001). Overall stoma rates were significantly lower in the CR group (40.4 versus 88.8%, P = 0.0001). Thirty‐day mortality was similar in both groups. Other secondary markers of morbidity including length of stay, return to theatre, anastomotic leak rate, wound problems and systemic complications had no significant difference between the two groups. Conclusion Subspecialist CR management of patients undergoing emergency left‐sided colonic resection on an acute surgical unit is associated with a similar level of morbidity and mortality while safely achieving significantly higher rates of primary anastomosis and lower stoma rates.